REPRESENTATION OF MORAL VALUES IN ONE ELT TEXTBOOK FOR SENIOR HIGH SCHOOL STUDENTS: CRITICAL DISCOURSE ANALYSIS - Dwi Widjaya Sukma; Elih Sutisna Yanto; Kusrin Kusrin (PROJECT (Professional Journal of English Education), 2021)
This study aims to investigate the depiction of moral values embedded in one ELT textbook specifically for XII grade senior high school endorsed by Indonesian Ministry of Educational and Culture. The authors use Critical Discourse Analysis (CDA) studies enlightened by Halliday’s (1978) Systemic Functional Linguistics (SFL) as data analysis. Since moral/character building becomes one of the priority programs prioritized by President Joko Widodo (Kemdikbud, 2017). Therefore, ELT textbooks must be in accordance with the program implied in the curricula. This critical discourse analysis focuses on analyzing visual objects and written texts adopting Kress and van Leuween’s (2006) visual grammar theory and Martin and white’s (2005) language appraisal theory to elaborate the moral values embedded with distinct genres in the textbook. The result shows that both visual and written texts with many genres in the textbook portraying a multitude of moral values. Thus, the implication of this study suggests both teachers and students should be able to acquire the necessary skills for critical thinking in reading and critical analysis of language sensitivity in order to understand the values. In addition, the analytical framework and the result of the research can be applied by the teachers and writers for explicit instruction, evaluation, and critical study of moral values in English language teaching. Keywords:  Critical Discourse Analysis; Moral Value; ELT Textbooks; Indonesian Moral Education